'I didn't have to tackle humungus people': An ecological investigation into a dispensation policy in New Zealand Junior Rugby. Issue 6 (December 2018) - Cassidy, Tania
The purpose of the study was to gain insight into the perceptions, experiences and practices of stakeholders, i.e. players, coaches and parents, involved in players being dispensated to play down a grade due to their small stature at one New Zealand metropolitan rugby union club. The discussion is organized around the perceptions, experiences, and practices of the various stakeholders and provides insight into how the various stakeholders perceive and experience the dispensation process. Bronfenbrenner's work was used to inform the design of the current study and the subsequent analysis because his ecological systems model of development is a generative and evolving conceptual framework for analysing human development throughout the life course as well as providing opportunities for development to be studied from the perspective of the person and their environment. The findings of this study provide insight for those involved in sports where playing numbers drop off round the teenage years. In addition, the findings contribute to further understanding the role emotions play in sport coaching, the 'birthdate effect', and 'relative age effect', the importance of developing connection, competence and confidence when focusing on youth development, the weight young people place on playing with friends as motivation to continue to playing sport.